Forgiveness : liberating or restraining? Exploring the constructions of forgiveness of people living with the Human Immunodeficiency Virus (HIV) - Viljoen, G.A. (University of Pretoria, 2013)
Dissertation (MA (Counselling Psychology))--University of Pretoria, 2007.